Associations of the serum kynurenine pathway metabolites with P50 auditory gating in non-smoking patients with first-episode schizophrenia - Yang, Qingyan; Zhang, Yong; Yang, Kebing; Niu, Yajuan; Fan, Fengmei; Chen, Song; Luo, Xingguang; Tan, Shuping; Wang, Zhiren; Tong, Jinghui; Yang, Fude; Li, Chiang-Shan R.; et al. (Frontiers in Psychiatry, 2022)
Objective Our study aimed to investigate the associations between the serum level of kynurenine pathway (KP) metabolites and P50 auditory gating in non-smoking patients with first-episode schizophrenia (FES). Materials and methods In this study, 82 non-smoking patients with FES and 73 healthy controls (HC). P50 auditory gating was measured using a fully functional digital 64-channel EEG system, and the components included S1 amplitude, S2 amplitude, gating ratio (S2/S1), and amplitude difference (S1–S2). Serum levels of kynurenine and kynurenine acid were assessed using a combination of liquid chromatography with tandem mass spectrometry. Psychopathology was assessed by the Positive and Negative Syndrome Scale (PANSS). Results The serum kynurenine (251.46 ± 65.93 ng/ml vs. 320.65 ± 65.89 ng/ml, t = –6.38, p < 0.001), and kynurenine acid levels (5.19 ± 2.22 ng/ml vs. 13.26 ± 4.23 ng/ml, t = –14.73, p < 0.001), S1 amplitude [2.88 (1.79, 3.78) μV vs. 3.08 (2.46, 4.56) μV, Z = –2.17, p = 0.030] and S1–S2 [1.60 (0.63, 2.49) μV vs. 1.92 (1.12, 2.93) μV, Z = –2.23, p = 0.026] in patients with FES were significantly lower than those in HC. The serum kynurenine and kynurenine acid levels were negatively associated with S1–S2 (r = –0.32, p = 0.004 and r = –0.42, p < 0.001; respectively) and positively correlated with S2/S1 ratio (r = 0.34, p = 0.002 and r = 0.35, p = 0.002; respectively) in patients. Conclusion Our findings suggested that neuroactive metabolites of the KP might play an important role in sensory gating deficit in first episode patients with schizophrenia. Furthermore, metabolites of the KP may be a new target for the treatment of cognitive impairments in schizophrenia.